Analysis of production area layout design based on lean and green thinking in the micro, small and medium enterprises (MSME) industry - Amrina, Uly; Oktora, Raden Adriyani; Widaningrum, Dyah Lestari; Mayangsari, Ika Devi (Universitas Serang Raya, 2024)
This research aims to analyze and design the layout of production areas based on Lean-Green (L&G) Thinking in Micro, Small and Medium Enterprises (MSMEs) Scale Companies. By focusing on operational efficiency and sustainable production processes, this research can help MSMEs increase their competitiveness in an increasingly competitive market. To support this goal, researchers used the Systematic Layout Planning (SLP) method combined with the Promodel 6.0 simulation tool. The SLP method helps in evaluating the current MSME layout system and identifying areas that can be made more efficient by considering the criteria of distance, time and electrical energy consumption. Meanwhile, simulation techniques are used to help formulate appropriate lean-green strategies to increase process efficiency and minimize environmental impacts. Evaluation of the company's current layout resulted in an increase in operational efficiency of 1.55%, a reduction in inventory of 83%, and a reduction in electricity consumption of 26%. This research recommendation includes concrete steps to improve the layout of production areas that support MSMEs to become agents of change that combine operational efficiency with environmental responsibility.